Pengaruh Latihan Otot Tungkai Terhadap Kemampuan 50 Meter Renang Gaya Dada Pada Ekstrakulikuler Renang Di Smk Bina Karya Utama Jakarta Timur - Muhammad Choirul Dzaki; Faridatul Ala; Asrori Yudha Prawira; Juli Candra (JOURNAL SAINS STUDENT RESEARCH, 2026)
Leg muscle strength training is one of the important factors in improving breaststroke swimming performance. The purpose of this study was to describe the effect of leg muscle training on 50-meter breaststroke swimming ability at SMK Bina Karya Utama. The method used in this study was a quantitative approach with an experimental method, aimed at determining the effect of a treatment on other variables under controlled conditions. The findings revealed that structured leg muscle training had a positive and significant impact on students' breaststroke swimming ability compared to routine training without a specific focus.